2017
DOI: 10.1080/10717544.2016.1259372
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing both oral bioavailability and brain penetration of puerarin using borneol in combination with preparation technologies

Abstract: Now there are few good oral preparations of puerarin used in cerebrovascular diseases because of its poor oral absorption caused by the low water solubility and the poor penetration into brain. In this study, three oral formulations of puerarin, nanocrystals suspension (NCS), inclusion compounds solution (ICS) and self-microemulsifying drug delivery system (SMEDDS) were prepared with borneol as an oral brain-targeting enhancer. A rat syngeneic in vitro model of the brain-blood barrier (BBB) was established to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…These results indicated that oral administration of PUE and TMP combined with borneol or α-asarone had an increased brain distribution. The previous study reported that borneol not only increased brain distribution but also increased oral absorption of PUE, but this study reported only enhanced brain distribution (Yi et al., 2017 ). This may be because the doses of PUE (20 mg/kg) and borneol (25 mg/kg) used in our study were relatively lower than the previous study (PUE: 200 mg/kg, borneol: 50, 100 and 200 mg/kg).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…These results indicated that oral administration of PUE and TMP combined with borneol or α-asarone had an increased brain distribution. The previous study reported that borneol not only increased brain distribution but also increased oral absorption of PUE, but this study reported only enhanced brain distribution (Yi et al., 2017 ). This may be because the doses of PUE (20 mg/kg) and borneol (25 mg/kg) used in our study were relatively lower than the previous study (PUE: 200 mg/kg, borneol: 50, 100 and 200 mg/kg).…”
Section: Resultsmentioning
confidence: 61%
“…Then a trans-endothelial electrical resistance (TEER) instrument (EVOM2, WPI, USA) was used to measure the TEER. The TEER value was increasing with cell proliferation, and when the value became consistent (>200 Ω cm 2 ) for seven consecutive days, the in vitro BBB was established (Yi et al., 2017 ; Zhu et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The authors proposed further studies on doses, schedules and combination regimens. Recently, borneol has been studied to increase both oral absorption and brain penetration of drugs in animal models 63 - 65 . Yi et al compared four different oral formulations of puerarin with borneol.…”
Section: Current Strategies To Deliver Drugs Into the Brainmentioning
confidence: 99%
“…Yi et al compared four different oral formulations of puerarin with borneol. Among them, a self-microemulsifying drug delivery system containing both puerarin and borneol resulted in significantly higher AUCs both in plasma and in the brain compared to other formulations 65 . It is very likely that co-administration of a drug and a permeability enhancer is insufficient to achieve the benefits of the enhancer in humans, as shown in the previous cereport and regadenoson studies.…”
Section: Current Strategies To Deliver Drugs Into the Brainmentioning
confidence: 99%
“…However, a suitable injection point should be optimized to avoid the peaks of the new sample overlapping the previous sample constituents. In the study, to avoid overlapping peaks, the nth (n > 1) injection point (t jn ) should satisfy equation (4).…”
Section: Hepm (V/v) Hepmwat (V/v) Hepemwat (V/v)mentioning
confidence: 99%